IHTIKAR IN HADITH: A FIQH AL-HADITH ANALYSIS OF HOARDING PRACTICES IN THE ISLAMIC ECONOMIC SYSTEM - Handika, Caca; Fithriany Rahmah, Yulia; Nurjaman, Ilham; Fauzi Nazar, Reza; Nurdiansyah, Irdan; Priyanti, Gita (Finansha: Journal of Sharia Financial Management, 2025)
The practice of hoarding goods poses a serious challenge to the realization of distributive justice within the Islamic economic system. This study aims to examine the prohibition of hoarding through a comprehensive fiqh al-hadith approach by tracing the legal status of relevant hadiths and analyzing the implications of hoarding practices for market dynamics and socio-economic stability. Employing a qualitative method with a descriptive-analytical design, this study is based on an extensive literature review that integrates tahrij al-hadith, syarh al-hadith, and a normative analysis grounded in maqasid al-shariah. The findings reveal that the prohibition of hoarding articulated in the hadith literature is not merely rooted in religious injunctions but also embodies profound ethical and social considerations that remain highly relevant to contemporary issues of goods distribution. Hoarding practices generate artificial scarcity, induce price inflation, and disrupt market equilibrium, ultimately imposing welfare losses on consumers. Accordingly, this study underscores the urgency of strengthening sharia-based regulatory oversight and enhancing public education on muamalah ethics as preventive measures against manipulative economic behavior. Overall, this study contributes to the development of a more just, ethical, and sustainable Islamic distribution framework in addressing the challenges of modern and globalized economies.